A Fresh Look at the Urbanisation in Kerala: Idea of Town Panchayats - Yacoub Zachariah Kuruvilla (KILA Journal of Local Governance, 2013)
Kerala is ranked second in percentage of urban population in major states of the country. In the context of rapid urbanization in Kerala, this paper outlines challenges that local governments will have to face. This paper also explores potential solutions for creating the necessary administrative and financial powers for local governments to meet these challenges, particularly rationale for constituting Town Panchayats in Kerala.